“SARENGHAE” as an Introduction to EPS-TOPIK Korean Language for Factory Workers in Tarumajaya Kertasari Village as Preparation for Employment in South Korea - Lia Amelia Nurkhazanah; Adhitya M. Maheswara; Indrati Asyariri; Syifa Fatimazzahroh (SWAGATI : Journal of Community Service, 2026)
The increasing investment of South Korean companies in Indonesia has created wider employment opportunities for Indonesian workers in industrial sectors related to Korean companies. However, access to Korean language learning based on industrial needs, especially Employment Permit System-Test of Proficiency in Korean (EPS-TOPIK), is still limited in rural areas. This community service activity aimed to introduce basic Korean language skills and Korean work culture to factory workers and the community in Tarumajaya Village, Kertasari District, Bandung Regency. The implementation methods included interactive lectures, discussions, and simple language practice focusing on Hangeul, industrial vocabulary, and basic workplace expressions. The results showed that participants gained a better understanding of Korean language basics, industrial communication, and Korean work culture. Participants also showed high enthusiasm and motivation to continue learning Korean as preparation for employment opportunities in Korean companies both in Indonesia and South Korea. Therefore, this activity is expected to become an initial step in improving community readiness and competitiveness in facing global industrial development.